Detection and quantification of pork and rat DNA in processed meats using multiplex quantitative Real‐Time PCR (m‐qPCR) (Indonesian Journal of Biotechnology, 2024)
In addition to the issue of pork contamination, processed meats frequently contain traces of rat meat. Therefore, detection and quantification of the pork and rat DNA in cases of meat and processed meat adulteration are necessary. In the current study, two gene targets of the cytochrome b for pigs and the Mt‐atp6 of Rattus norvegicus for rats were used in the absolute multiplex quantitative real‐time PCR (m‐qPCR). The sample DNA was amplified with a standard as positive control in the various concentration of 1000 pg, 100 pg, 10 pg, 0.1 pg, 0.01 pg, and 0.001 pg. There were 25 processed meat samples and 5 fresh meat samples identified in this study. Among the total of 30 samples assessed, 6 samples were successfully detected and quantified their pork and rat DNA contamination. One sample was contaminated with pork DNA with a concentration of 2.451×10‐4 pg (“Meatball 3). Five samples were contaminated with rat DNA with a concentration of 3.603×10‐11 pg (“Sempol 3”), 2.196×10‐10pg (“Meatball 6”), 4.908×10‐11 pg (“Siomay 3”), 1.489×10‐10 pg (“Grinding 2”), and 3.564×10‐10 pg (“Grinding 4”). In this study, we have discovered that the contamination of pork and rat were detected in the samples. It suggested that this method is applicable for detecting the contaminant in processed meat samples